Characterization of Hepatic Tumors: Value of Contrast-Enhanced Coded Phase-Inversion Harmonic Angio - Wen, Yan Ling; Kudo, Masatoshi; Zheng, Rong Qin; Ding, Hong; Zhou, Pei; Minami, Yasunori; Chung, Hobyung; Kitano, Masayuki; Kawasaki, Toshihiko; Maekawa, Kiyoshi (American journal of roentgenology (1976), 2004)
Our purpose was to evaluate the value of contrast-enhanced coded phase-inversion harmonic imaging in showing the characteristic intranodular hemodynamics of hepatic tumors. SUBJECTS AND METHODS. Using a microbubble contrast agent we performed coded harmonic angio in 163 patients with 192 hepatic tumor nodules: 153 hepatocellular carcinomas, 13 metastases, 14 hemangiomas, eight dysplastic nodules, and four focal nodular hyperplasias. After injecting Levovist, we performed real-time scanning, interval-delay fast low-angle shot imaging, and sweep scanning in the early arterial phase, late vascular phase, and postvascular phase, respectively. On contrast-enhanced coded harmonic angio, the typical hemodynamic pattern of hepatocellular carcinomas was shown as abundant tumor vessels supplied from the periphery to the center of the tumor and dense parenchymal tumor staining with fast washout (sensitivity, 92.8%; specificity, 92.3%). The characteristic hemodynamic pattern of metastases was peripheral tumor vessels with a rim parenchymal stain in the vascular phase followed by a perfusion defect in the postvascular phase (sensitivity, 69.2%; specificity, 100%). Hemangiomas were hypovascular in the early arterial phase with gradual spotty or cotton-wool pooling continuing to the late vascular phase (sensitivity, 92.9%; specificity, 100%). Dysplastic nodules were shown as having no early arterial supply with isovascularity in the late vascular phase (sensitivity, 75%; specificity, 100%). Focal nodular hyperplasias were shown to have a spoked wheel pattern of blood vessels accompanied by dense staining in interval-delay scanning (sensitivity, 100%; specificity, 100%). Contrast-enhanced coded harmonic angio is a promising method to provide useful information for the differential diagnosis of hepatic tumors.